(3GdhLjR aj abg GdSfI hGdcJGH GdYRjRs - (3GdNdjaj, YHO GdYXje Hf HOhjs; (3fhQ GdOjf, eMeO UahJs; (3GdThGOaj, eMeO UahJ CMeO jhSa,s 1375-1421 (3g`(B.s ((3GdbGgQI (B:s (3OGQ GHf QLH ddfTQ hGdJhRjY,s, 2009)
(3Gdabg GdESdGej(B.s
Keywords: (3Gdabg GdESdGejs